Study on Liposomes Integrity and Delivery of siRNA to Lung Cancer - Aljasser, Abdullah (2024)
The thesis focuses on studying liposomes' structural integrity and their interactions with model and plasma cellular membrane in vitro, utilizing fluorescence resonance energy transfer (FRET) as a key analytical tool. The study comprises the fabrication and physicochemical characterization of liposomes, the influence of α-linolenic acid incorporation on their properties and liposomes - cell interactions, and the potential of liposomes as siRNA delivery vehicles for lung cancer treatment. The initial phase of this research involved the fabrication of liposomes from various lipid and optimization of incorporation of DiO and DiI as fluorescent FRET pair probes. The successful embedding of these fluorophores within the liposomal membrane was confirmed by the observed quenching of donor emission and enhancement of acceptor emission. A key focus then moved to the role of an incorporation of an unsaturated fatty acid, α-linolenic acid, into liposomal membrane and the assessment of its potential fusogenic behavior. Through physicochemical characterizations the study evaluated dye incorporation efficiency, liposomal content leakage, and membrane fluidity. The findings revealed that liposomal membrane fluidity increases with the increase of α-linolenic acid content in liposomes. Data further show that on interaction with a membrane model liposome, the FRET ratio for DiO&DiI probes embedded in different liposome formulations decreased, suggesting vesicle membrane mixing / fusion. No significant carboxyfluorescein leakage from liposomes was observed with up to 30 mol% of α-linolenic acid, indicating their integrity in suspension. These observations establish the foundation for further investigations into the fusion behavior of fabricated liposomes at the cellular level. In the second chapter, the focus was on the impact of α-linolenic acid on liposome - cell interactions. Metabolic activity analysis revealed that liposomes without α-linolenic acid (αLA0) were non-toxic, whereas those with 20 mol% α-linolenic acid (αLA20) displayed dose-dependent cytotoxicity. FRET measurements data indicate that α-linolenic acid incorporation notably increased cell-associated fluorescence, indicating its significant influence on liposome - cell interactions. Both αLA0 and αLA20 liposomes demonstrated a reduction in FRET ratio upon interaction with A549 cells, suggesting membrane mixing or perturbations in liposome membrane integrity. Interestingly, the incorporation of α-linolenic acid resulted in pronounced liposome accumulation at/within A549 cell plasma membrane, as evidenced by localization patterns (Pearson’s correlation coefficient values) in confocal microscopy. These observations highlight the role of α-linolenic acid in enhancing liposomal interaction with cellular plasma membrane. The final chapter explored the feasibility of using liposomes as siRNA delivery vehicles, particularly in lung cancer cells. Due to its impact on liposomes formation in the presence of negatively charged siRNA and cationic lipid DOTAP, α-linolenic acid was excluded from this phase. The encapsulation efficiency of siRNA within liposomes was determined, revealing high encapsulation (> 90%) with liposomes containing 30 mol % DOTAP with N/P ratio of 9. The cytotoxicity assay demonstrated a concentration-dependent effect of DOTAP liposomes on A549 cells. A total lipid concentration greater than 20 mM was found to be toxic, resulting in less than 10% cell viability. In contrast, concentrations below 4 mM were observed to have minimal or no effect on cell viability. Successful cellular uptake of siRNA was demonstrated through flow cytometry and confocal microscopy. The efficiency of liposomal formulations in gene silencing was confirmed by luciferase gene silencing assays on A549-luciferase cells, with different DOTAP liposomes formulations showing significant activity reductions (‘silencing’) compared to control, scrambled siRNA liposomes. These findings highlight the potential of designed DOTAP/siRNA liposomes as a feasible approach to siRNA delivery and targeted gene silencing. To conclude, the thesis aims to provide understanding of the behavior of liposomes incorporating α-linolenic acid, particularly in the context of a potential lung therapy. The study gains understanding on the structural integrity of liposomes upon their interactions with model and cellular membranes, utilizing the FRET technique as a main investigative tool. It points to the potential of incorporating different 'helper’ lipids to influence interactions of liposomes with cells and consequently influence the delivery of cargo loaded into the liposome.